Market timing with option-implied distributions in an exponentially tempered stable Lévy market - Guerra, João (2019)
This paper explores the empirical implementation of a dynamic asset allocation strategy using option-implied distributions when the underlying risky asset price is modeled by an exponential Lévy process. One month risk-neutral densities are extracted from option prices and are subsequently transformed to the risk-adjusted, or real-world densities. Optimal portfolios consisting of a risky and risk-free asset rebalanced on a monthly basis are then constructed and their performance analyzed. It is found that the portfolios formed using option-implied expectations under the Lévy market assumption, which are flexible enough to capture the higher moments of the implied distribution, are far more robust to left-tail market risks and offer statistically significant improvements to risk-adjusted performance when investor risk aversion is low, however this diminishes as risk aversion increases.